VARIASI BAHASA PADA MAHASISWA PERANTAU DI FAKULTAS ILMU BUDAYA UNIVERSITAS MULAWARMAN: KAJIAN SOSIOLINGUISTIK - Wati, Usnia; Rijal, Syamsul; Hanum, Irma Surayya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The occurrence of language variations is not only caused by diverse speakers, but because the social interaction activities carried out are also very diverse. In this case there is a connection with the emergence of languages used by overseas students, and usually these languages appear in their activities on campus. The use of the first language and dialect that affect their language conditions, resulting in incomplete use of the Indonesian language. However, regional languages are also not the only concrete evidence that there are variations in language that occur among overseas students. But the emergence of several variations of the language used by overseas students. This study aims to describe the language variations and factors that cause variations in the language of foreign students in Indonesian Literature class of 2014 at the Faculty of Cultural Sciences, Mulawarman University. This research includes field research using qualitative descriptive methods. The research method used is the method of referring to the technique of observation, record, and note, while the method of proficiency with a fishing line and proficient techniques. The method used to analyze the data in this study is the padan method using the basic technique of PUP (sorting determinants). The results showed that the language used by students of Indonesian Literature nomads in 2014 at the Faculty of Cultural Sciences, Mulawarman University varied greatly. Language variations in terms of speakers, variations in language in terms of usage, variations in language in terms of formality, and variations in language in terms of means. The factors that cause variations in the language of foreign students in the 2014 Indonesian Literature Faculty of Cultural Sciences, Mulawarman University are social factors and situational factors. Social (environmental) and situational factors (linguistic and kinship situations).